Rheological study of the thermoreversible sol-gel transition of sulfate modified zirconyl chloride aqueous sol - Sanhueza, CSS; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier B.V., 2004)
The sols prepared by mixing a ZrOCl2 acidified solution to a hot H2SO4 aqueous solutions were studied in order to clarify the mechanism of thermoreversible sol-gel transition observed in this system. The viscoelastic properties of these suspensions were analyzed during the sol-gel transition by dynamic rheological measurements and quasi-elastic light scattering. The rheological properties were correlated to mass fractal and nearly linear growth models, and percolation theory. The results evidence that the thermoreversible sol-gel transition in this system is due to the formation of a network of physically linked aggregates having fractal structure. The decrease of the SO42- contents in the initial solution leads to the decrease of the fractal dimensionality from 2.3 to 1.8, indicating a change of the kinetic mechanism of aggregate growth. Near the gel point these samples have the typical scaling expected from percolation theory. (C) 2004 Elsevier B.V. All rights reserved.